Islamic da'wah in minority Muslim countries: a case study on Japan and Korea - Fathil, Fauziah; Fathil, Fathiah (Department of Islamic History and Civilization, Academy of Islamic Studies, UM, 2011)
Little has so far been discussed or written on Islam and Muslims in Japan, even less so on Islam and Muslims in Korea. This is in marked contrast to nearby China, which, though is also a Muslim minority country attracted a wide attention from scholars of either Muslim or non-Muslim world. The reason is clear, that is, unlike China which consists of a sizeable number of Muslims, Muslim communities in both Japan and Korea is exceedingly small. This paper attempts to provide the much lacking information on the spread and development of Islam in these two countries, hoping that future research on the topic will be pursued by others in acquainting ourselves with fellow Muslims in Japan and Korea. To begin with, the paper will analyze the coming of Islam, the means through which Islamization process took place, and the establishment of Muslim communities in Japan and Korea. Special attention will then be given to the factors which contributed to Islamic da’wah in both countries including the role of Muslim da’i, foreign and local, Muslim organizations, etc. Equally important to discuss is the contribution of overseas Muslim individuals, Muslim countries and international Islamic organizations in facilitating the da’wah movement in Japan and Korea. Next, the challenges and problems faced by the da’wah movement will be examined as they might explain the reasons for the minute number of Muslim population and the slow progress of Islamic da’wah in the countries. This is crucial since necessary actions can then be taken or solutions be sought to ensure smooth progress of da’wah activities in Japan and Korea. Finally, the prospects of Islamic da’wah will be discussed together with the reactions of the Japanese and Korean government towards Islam and Muslim population in the countries. In doing so, the impacts and outcomes of decades of da’wah in Japan and Korea can be assessed and this could also provide impetus for Muslims to find ways in promoting Islam further in these two East Asian nations.